GRAMMATICAL CHARACTERISTICS OF AUXILIARY WORD GROUPS: CONJUNCTIONS - Berdikulova Shakhnoza Ruzikulovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the grammatical features of the auxiliary, conjunction, and predicate, their differences, similarities, origin, and usage will be discussed.